Targeting Postprandial Hyperglycemia With Physical Activity May Reduce Cardiovascular Disease Risk. But What Should We Do, and When Is the Right Time to Move? - Solomon, Thomas P. J.; Eves, Frank F.; Laye, Matthew J. (Frontiers in Cardiovascular Medicine, 2018)
Physical inactivity and excessive postprandial hyperglycemia are two major independent risk factors for type 2 diabetes and cardiovascular-related mortality. Current health policy guidelines recommend at least 150 minutes of physical activity per week coupled with reduced daily sedentary behavior by interrupting prolonged sitting with bouts of light activity every 30-minutes. This evidence-based strategy promotes health and quality of life. Since modern lifestyle enforces physical inactivity through motorized transportation and seated office working environments, this review examines the practical strategies (standing, walking, stair climbing, and strength-based circuit exercises) for reducing sitting time and increasing activity during the workday. Furthermore, since postprandial hyperglycemia poses the greatest relative risk for developing type 2 diabetes and its cardiovascular complications, this review examines a novel hypothesis that interrupting sitting time would be best focused on the postprandial period in order to optimize blood glucose control and maximize cardiometabolic health. In doing so, we aim to identify the science gaps which urgently need filling if we are to optimize healthcare policy in this critical area.